Pre-pregnancy obesity and non-adherence to multivitamin use: findings from the National Pregnancy Risk Assessment Monitoring System (2009–2011). Issue 1 (December 2016) - Masho, Saba; Bassyouni, Amani; Cha, Susan
Abstract Background Although adequate folic acid or multivitamins can prevent up to 70 % of neural tube defects, the majority of U.S. non-pregnant women of childbearing age do not use multivitamins every day. Factors influencing consistent multivitamin use are not fully explored. This study aims to investigate the association between pre-pregnancy body mass index (BMI) and multivitamin use before pregnancy using a large, nationally representative sample of women with recent live births. Methods The national 2009–2011 Pregnancy Risk Assessment Monitoring System data were analyzed. The sample included women with recent singleton live births (N = 104, 211). The outcome of interest was multivitamin use which was categorized as no multivitamin use, 1–3 times/week, 4–6 times/week, and daily use. Maternal BMI was examined as underweight (<18.50 kg/m2 ), normal weight (18.50–24.99 kg/m2 ), overweight (25.00–29.99 kg/m2 ), and obese (≥30.00 kg/m2 ). Multinomial logistic regression was conducted, and adjusted odds ratios and 95 % confidence intervals were calculated. Results Compared to women with normal weight, overweight and obese women had significantly increased odds of not taking multivitamins after adjusting for confounding factors. Further, the lack of multivitamin use increased in magnitude with the level of BMI (ORoverweight = 1.2, 95 % CI = 1.1–1.3; ORobese = 1.4, 95 % CI = 1.2–1.5). Conclusions Obese and overweight women were less likely to follow the recommendation for preconception multivitamin use compared to normal weight women. All health care professionals must enhance preconception care with particular attention to overweight and obese women. Preconception counseling may be an opportunity to discuss healthy eating and benefits of daily multivitamin intake before pregnancy.